2020
DOI: 10.3389/fmicb.2020.00386
|View full text |Cite
|
Sign up to set email alerts
|

NopD of Bradyrhizobium sp. XS1150 Possesses SUMO Protease Activity

Abstract: Effectors secreted by the type III protein secretion system (T3SS) of rhizobia are hostspecific determinants of the nodule symbiosis. Here, we have characterized NopD, a putative type III effector of Bradyrhizobium sp. XS1150. NopD was found to possess a functional N-terminal secretion signal sequence that could replace that of the NopL effector secreted by Sinorhizobium sp. NGR234. Recombinant NopD and the C-terminal domain of NopD alone can process small ubiquitin-related modifier (SUMO) proteins and cleave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 57 publications
(90 reference statements)
0
29
0
Order By: Relevance
“…Recently, NopD of Bradyrhizobium sp. XS1150 appears as characterized rhizobial SUMO protease facilitates a symbiotic efficiency 31 . ULP1 active-site function depends on the sequentially ordered catalytic-core triad His-Asp-Cys 32 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, NopD of Bradyrhizobium sp. XS1150 appears as characterized rhizobial SUMO protease facilitates a symbiotic efficiency 31 . ULP1 active-site function depends on the sequentially ordered catalytic-core triad His-Asp-Cys 32 .…”
Section: Resultsmentioning
confidence: 99%
“…The XopD effector was originally identified from Xcv., which causes spot disease on tomato and pepper plants, while the NopD restricts nodulation of Tephrosia vogelii by Bradyrhizobium sp. XS1150 31,56 . In the present study, we showed that the Bel2-5 positively regulates the activation of soybean nodulation signalling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bel2-5 shares similarity with the rhizobial T3E NopD ( Xiang et al, 2020 ) and with XopD ( Noël et al, 2002 ), from the plant pathogen Xcv . ( Ratu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…ORS3257 ( Teulet et al, 2019 ), and NopD of Bradyrhizobium sp. XS1150 ( Xiang et al, 2020 ). However, whether their cellular/symbiotic activities depend on nuclear localization remains unknown.…”
Section: Discussionmentioning
confidence: 99%